2022
DOI: 10.1039/d1tb02233d
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the bactericidal mechanism of Cu(OH)2 nanorods in water through Mg-substitution: high production of toxic hydroxyl radicals by non-soluble particles

Abstract: To date, there is still a lack of definite knowledge regarding the toxicity of Cu(OH)2 nanoparticles towards bacteria. This study was aimed at shedding light on the role played by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The limited 2 θ range and resolution of NPD patterns of the x = 0.2 sample does not allow the amount of MgO present to be accurately quantified by refinement using the Rietveld method. 29 In our previous study (thanks in particular to thermal analyses), 17 we found that the solubility limit of Mg 2+ ions in Cu(OH) 2 is 10 mol% ( i.e. Cu 0.9 Mg 0.1 (OH) 2 ).…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…The limited 2 θ range and resolution of NPD patterns of the x = 0.2 sample does not allow the amount of MgO present to be accurately quantified by refinement using the Rietveld method. 29 In our previous study (thanks in particular to thermal analyses), 17 we found that the solubility limit of Mg 2+ ions in Cu(OH) 2 is 10 mol% ( i.e. Cu 0.9 Mg 0.1 (OH) 2 ).…”
Section: Resultsmentioning
confidence: 82%
“…Prior to decomposition, we checked by EDX analysis that the precursor particles had the expected Mg/Cu atomic ratio. 17 X-ray powder diffraction (XRPD) patterns were recorded after decomposition to determine the phase purity of as-obtained powders. In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations